Transimperial Sociology: A Peripheral Dictatorship at the Centre of Late Colonial Social-Scientific Cooperation Between Empires - Ágoas Frederico (HoST)
This text presents a thick description of Portuguese colonial science policy and diplomacy during the era of decolonization with a focus on the social sciences. By examining archival materials from institutions responsible for monitoring Portuguese participation in transimperial organizations for scientific cooperation, it elucidates social-scientific initiatives within the empire and the epistemic and institutional motivations that shaped them, while also providing insight into how these forums interacted across global and imperial contexts. In doing so, the article illuminates the factors that, beyond political circumstances, both drove and delayed the paradigmatic shift in Portuguese colonial science from physical anthropology toward the social sciences. Additionally, it provides a unique, overarching view of these central yet often overlooked actors in the international arena, highlighting their social-scientific drifting, beyond their differences and specificities. This approach holds intrinsic value as it contributes to the history of the Portuguese empire and to the study of late colonialism, underscoring the central role of the social sciences in renewing and legitimizing imperial governance. Additionally, it serves as a case study in the historical sociology of knowledge, expanding on scholarship that has explored the intersection of authoritarianism and imperialism in the natural sciences but not in the social sciences. In terms of the latter, this approach also highlights some of the material and symbolic determinants behind the rise of sociology and social anthropology in Africa, adding a transimperial layer to studies that have explored their colonial origins.